Curcumin alleviates rheumatoid arthritis-induced inflammation and synovial hyperplasia by targeting mTOR pathway in rats - Dai QD; Zhou D; Xu LP; Song XW (Dove Medical Press, 2018)
Qiaoding Dai,1 Di Zhou,2 Liping Xu,1 Xinwei Song1 1Department of Rheumatology and Immunology, First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou 310006, Zhejiang, People’s Republic of China; 2Nephrology Department, First People’s Hospital of Xiaoshan District, Hangzhou 311200, Zhejiang, People’s Republic of China Purpose: Rheumatoid arthritis (RA) is a chronic, progressive autoimmune disease characterized by aggressive and symmetric polyarthritis. Mammalian target of rapamycin (mTOR) was reported to be a new target for RA therapy and its inhibitor rapamycin can significantly reduce the invasive force of fibroblast-like synoviocytes. Here, we determined the effect of curcumin to alleviate inflammation and synovial hyperplasia for the therapy of RA.Materials and methods: Collagen-induced arthritis (CIA) was developed in Wistar rats and used as a model resembling RA in humans. Rats were treated with curcumin (200 mg/kg) and the mTOR inhibitor rapamycin (2.5 mg/kg) daily for 3 weeks. Effects of the treatment on local joint, peripheral blood, and synovial hyperplasia in the pathogenesis of CIA were analyzed.Results: Curcumin and rapamycin significantly inhibited the redness and swelling of ankles and joints in RA rats. Curcumin inhibited the CIA-induced mTOR pathway and the RA-induced infiltration of inflammatory cells into the synovium. Curcumin and rapamycin treatment inhibited the increased levels of proinflammatory cytokines including IL-1β, TNF-α, MMP-1, and MMP-3 in CIA rats.Conclusion: Our findings show that curcumin alleviates CIA-induced inflammation, synovial hyperplasia, and the other main features involved in the pathogenesis of CIA via the mTOR pathway. These results provide evidence for the anti-arthritic properties of curcumin and corroborate its potential use for the treatment of RA. Keywords: rheumatoid arthritis, curcumin, rapamycin, mammalian target of rapamycin, collagen-induced arthritis